"Tradition, rationality, and change: Essays in sociology of economic development and social change" - Rao, M.S.A (Bombay, 1972)
The first four chapters in this Volume deal with the socio- logical aspects of economic development. The first of these considers the adjustments and consequences incumbent upon the introduction of development programmers in village communities. The very objective of the community development programme is oriented to the modern or 'rational' needs of development in so far as these are made felt in the rural It is but desirable to expect, in the interest of the development schemes, the presence of certain prerequisites such as rationality of outlook, belief in the principle of equality, That it is precisely these sector. and modern cooperative action. features that are absent in the traditional social structure is something which is often overlooked by the planners. The planners expect co-operation on the basis of equality when in reality, the nature of co-operation found in the village community is based on hierarchy and inequalities. But on the whole, it has been found that despite the absence of the exact prerequisites of growth the traditional institutions of caste and joint family have acquired, to some extent, the flexibility to perform new functions and to fulfil new expectations.